Incidence and risk factors for new-onset atrial fibrillation following coronary artery bypass grafting: A systematic review and meta-analysis. (October 2020) - Higgs, Megan; Sim, Jenny; Traynor, Victoria
Abstract: Objectives: To estimate the incidence of new-onset post-operative atrial fibrillation after isolated coronary artery bypass surgery and summarise the evidence on risk factors that predispose people to developing the complication. Study design/methods: A systematic review was conducted to identify studies from the CINAHL, MEDLINE and Cochrane databases. A title and abstract review was conducted by one reviewer. Full text review and quality assessment processes were conducted by two reviewers. Incidence data was combined in meta-analysis using the 'metaprop' routine in Stata and risk factor data were synthesised in narrative and table format. Results: Ten studies, including 6173 participants, were included in the review. The estimated pooled incidence of post-operative atrial fibrillation was 25% (CI 0.19–0.30). In a secondary meta-analysis including studies that only included first time bypass surgery recipients the estimated pooled incidence was 26% (CI 0.14–0.41). Due to high levels of heterogeneity these results should be interpreted with caution. Risk factors with the strongest associations to post-operative atrial fibrillation were chronic obstructive pulmonary disease, decreased partial pressure of oxygen on air, congestive heart failure, right coronary artery disease, male gender, prolonged cross clamp time and port-operative inotropic exposure. Conclusion: Further prospective studies are needed to strengthen the current evidence base.